Effect Of Financial Distress On Tax Aggressiveness With Company Reputation As A Moderating Variable - Wijaya, Suparna; Syarifah, Naili Luthfi (WIM Solusi Prima, 2024)
One of the obstacles faced in collecting tax revenues is the practice of tax aggressiveness by the company. In conditions of financial constraints, the strategy of saving cash for taxes is the manager's main choice to maintain company cash because it does not have a bad impact on company operations. The company's reputation is an intangible asset that is seen as important to improve the company's performance so as to encourage business sustainability and the quality of the company's future. The purpose of this study was to examine the effect of financial distress on tax aggressiveness with the company's reputation as moderating. The method used is quantitative with the object of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The results of the study indicate that financial distress has a positive effect on tax aggressiveness. The company's reputation is not able to weaken the positive influence of financial distress on tax aggressiveness.